Synergy In-Line Skates and Cafe / Mohd Afendy Md. Yazim ... [et al.] - Md. Yazim, Mohd Afendy; Raup, Mohd Zool Hilmi; Mahat, Mazlihin; Mohd Iskah, Nazri; Yusof, Abdullah (Faculty of Office Management & Technology, 2001)
To provide affordable and excellent health and fitness through a high standard of professionalism and the use of up-to-date innovation that is using latest skating equipment in the market and equipped with sophisticated point of sale system.